Export variety, technological content and economic performance: The case of Portugal - Silva, Ester Gomes da (2013)
Although the analysis of the relationship between international trade and economic growth has an important tradition in the economic literature, the specific focus on a related matter, the link between export variety and economic growth, remains a relatively unexplored field of research. Recently, a few studies have approached this issue, adopting a neo-Schumpeterian framework. In line with this general frame of analysis, in this paper we investigate the impact of export variety on economic growth, cross-relating the variety dimension with technological upgrading. Cointegration econometric results based on the Portuguese experience over the past four decades (1967-2010) show that increased related variety has led to a significant growth bonus, but only in the case of technology advanced sectors. The impact of export variety on economic performance seems, therefore, to be conditioned by the technological intensity of the products involved.